WHOLEGRAIN FLOURS OF DIFFERENTLY COLORED MAIZE KERNELS AS MACRO- AND MICRONUTRIENT-RICH FOOD INGREDIENTS - Nikolić, Valentina (Journal on Processing and Energy in Agriculture, 2022)
Four commercial wholegrain flours made from differently colored kernels of maize genotypes produced in Maize Research Institute "Zemun Polje" were used as the subject of this study. Values of major chemical components as well as mineral nutrients, antioxidants, and some vitamins of wholegrain flours obtained from white dent hybrid, yellow popping maize hybrid, red dent variety, and blue popping maize population are presented. All flours had high fiber content (6.9-10.4%), while total protein ranged from 8.5% to 12.2%. A high level of anthocyanins was determined in blue popping maize wholegrain flour (910.0 mg CGE/kg), whereas yellow popping maize flour had a high content of total carotenoids (26.5 mg βCE/kg). Total antioxidant capacity was the lowest in white (15.50 mmol Trolox Eq/kg) and the highest in blue popping maize flour (37.6 mmol Trolox Eq/kg). All investigated wholegrain flours contained high levels of potassium and magnesium, as well as high content of trace elements, namely iron, zinc, copper, and manganese. The maize flour is naturally gluten-free, which makes it highly suitable for persons susceptible to a gluten allergy and those with celiac disease. These results indicate that the wholegrain ZP maize flours can be used as functional food ingredients with potential health benefits.